Placebo effect after visual restitution training: no eye-tracking controlled perimetric improvement after visual border stimulation in late subacute and chronic visual field defects after stroke - Leitner, Michael Christian; Ladek, Anja-Maria; Hutzler, Florian; Reitsamer, Herbert; Hawelka, Stefan (Frontiers in Neurology, 2023)
A significant number of Restitution Training (RT) paradigms claim to ameliorate visual field loss after stroke by re-activating neuronal connections in the residual visual cortex due to repeated bright light-stimulation at the border of the blind and intact fields. However, the effectiveness of RT has been considered controversial both in science and clinical practice for years. The main points of the controversy are (1) the reliability of perimetric results which may be affected by compensatory eye movements and (2) heterogeneous samples consisting of patients with visual field defects and/or visuospatial neglect. By means of our newly developed and validated Virtual Reality goggles Salzburg Visual Field Trainer (SVFT) 16 stroke patients performed RT on a regular basis for five months. By means of our newly developed and validated Eye Tracking Based Visual Field Analysis (EFA), we conducted a first-time full eye-movement-controlled perimetric pre-post intervention study. Additionally, patients subjectively rated the size of their intact visual field. Analysis showed that patients' mean self-assessment of their subjective visual field size indicated statistically significant improvement while, in contrast, objective eye tracking controlled perimetric results revealed no statistically significant effect. Thus, bright-light detection RT at the blind-field border solely induced a placebo effect and did not lead to training-induced neuroplasticity in the visual cortex of the type needed to ameliorate the visual field size of stroke patients.